Peace Education Berbasis Kearifan Lokal: Membaca Peran Perempuan Tengger melalui Lensa Pendidikan Islam Inklusif - Amang Fathurrohman; Ida Rochmawati; Imroatul Azizah; Moh. Irmawan Jauhari; Alimul Muniroh (Tarbawi : Jurnal Studi Pendidikan Islami, 2025)
Purpose: This study aims to explore the strategic role of Tengger women in early conflict detection within religious dynamics in Tosari District, Pasuruan, and to examine how their practices can be understood through the framework of inclusive Islamic peace education. Design/methodology/approach: This research employs a qualitative approach with Miles and Huberman’s interactive analysis model. Data were collected through three months of participatory observation, in-depth interviews with 35 key informants, and focus group discussions (FGDs) with local women's forums, traditional leaders, and religious figures. Research limitations/implications: The study is limited to the Tengger community in Tosari District, East Java. However, the findings provide valuable insights into the development of culturally sensitive and gender-responsive peace education models for multicultural societies and offer practical implications for inclusive Islamic education. Findings: The results reveal how Tengger women activate local wisdom values such as sayan (mutual cooperation) and setuhu (commitment to harmony) as social vigilance mechanisms. Their unique position in traditional social structures enables them to develop effective early warning systems through informal networks and community activities. The study further constructs a critical dialogue between these indigenous practices and Islamic educational principles such as ta'awun (cooperation), ukhuwah (brotherhood), and rahmatan lil 'alamin (mercy to all creation). Originality/value: This research contributes to peace education literature by documenting an organic, community-based model of peace education developed and practiced by indigenous women. It offers a transformative framework for Islamic peace education that integrates cultural wisdom, gender responsiveness, and religious values, providing an alternative model for educational institutions in multicultural contexts